Recent Developments in Solid-Phase Glycan Synthesis - Huang, Jhih-Yi; Delbianco, Martina (Synthesis, 2022)
Solid-phase glycan synthesis (SPGS) is a valuable approach to access broad collections of complex, well-defined oligo- and polysaccharides in short amounts of time. The target structure is assembled following iterative cycles of glycosylation and deprotection, often aided by automated machines. To expand the scope of SPGS, new solid supports, linkers, glycosylation and deprotection reactions, and functionalization strategies are constantly being developed. Here we discuss the state of the art of SPGS, with particular focus on the chemistry happening on solid-phase. We highlight recent achievements as well as challenges to be addressed to expand the scope of SPGS even further.1 Introduction2 Solid-Phase Glycan Synthesis2.1 The Solid Support2.2 The Linker2.3 The Assembly Process2.4 Post-Assembly Manipulations2.5 The Analysis2.6 Cleavage from the Solid Support3 Conclusion and Outlook
Keywords: solid-phase synthesis; glycans; carbohydrates; automated glycan assembly